Compositional design and crystallization mechanism of High Bs nanocrystalline alloys. (April 2019) - Liu, Tao; Wang, Anding; Zhao, Chengliang; Yue, Shiqiang; Wang, Xinmin; Liu, C.T.
Graphical abstract: Highlights: The effects of constituent elements on AFA and grain refinement were analyzed. FeSiBPCCu alloys were designed according to the proposed composition design rules. Preformed Cu-clusters can stimulate the crystallization process. Suitable Cu content is essential for uniform structure and excellent properties. Changes of magnetic properties is well explained by the microstructure evolutions. Abstract: High B s nanocrystalline alloys (HBNAs) are increasingly attractive due to their unique microstructure and outstanding magnetic properties. It is important to clearly explore the crystallization mechanism to provide reliable and efficient composition design methods. In this study, composition design rules are proposed under the considerations of high amorphous forming ability (AFA) and microstructure refinement. These rules were verified in designing a FeSiBPCCu alloy system with excellent magnetic performance. The crystallization mechanism was investigated by exploring the microstructure evaluation process and the effects of Cu on the nucleation and crystallization processes. The addition of Cu stimulates the crystallization process, leading to the formation of a uniform microstructure with fine grains. The microstructure evaluation process was also clearly exhibited, which could explain the changes in the magnetic properties during the annealing process. The results are of great significance and shed light on the crystallization mechanism of HBNAs.